2021
DOI: 10.22302/iribb.jur.mp.v89i2.458
|View full text |Cite
|
Sign up to set email alerts
|

Inisiasi, pertumbuhan, dan perkembangan kalus embriogenik tanaman stevia (Stevia rebaudiana)

Abstract: The leaves of sweetener plant Stevia rebaudiana contain secondary metabolites of steviol glycosides which are very sweet, with no calorie and zero glycemic index. Propagation of stevia by seeds is ineffective due to its low germination rate and diverse progenies. The tissue culture of stevia can be used to mass propagate rapidly and is commonly conducted by shoot multiplication. Up to now, the technology of somatic embryogenesis (SE) in stevia has not been successful yet. SE is developed to increase the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…While the interior shoots that were still white and cut into 0.5 cm pieces were used as explants in this study, the outer shoots were not used. More than 70% of stevia plant clone BX leaf, book, and internode explants successfully initiated callus formation [5].…”
Section: Sampling and Callus Inductionmentioning
confidence: 98%
“…While the interior shoots that were still white and cut into 0.5 cm pieces were used as explants in this study, the outer shoots were not used. More than 70% of stevia plant clone BX leaf, book, and internode explants successfully initiated callus formation [5].…”
Section: Sampling and Callus Inductionmentioning
confidence: 98%
“…However, there are still some bottlenecks in the oil palm SE, such as low efficiency of SE induction and regeneration [6], and the risk of somaclonal variation resulting in abnormal planting materials [7]. Although many improvements in the initial steps of SE have successfully enhanced callus formation and somatic embryos expression [1,2], the somatic embryos' germination into shoots, and further development into plantlets is often problematic, such as low germination rate and occurrence of shoot tip necrosis [8]. Monteiro et al [9] reported that the maximum regeneration rate of oil palm somatic IOP Publishing doi:10.1088/1755-1315/1308/1/012005 2 embryos was around 50% for the best treatments.…”
Section: Introductionmentioning
confidence: 99%